DO CASH FLOWS AND BANK SIZE INFLUENCE STOCK RETURNS? - Sari, Bella Mega; Espa, Vitriyan; Dosinta, Nina Febriana (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This research aims to determine the effect of cash flow statement components and bank size on stock returns. This study uses a signaling and stakeholder theory approach in the banking sector companies listed on the Indonesian stock exchange for 2017-2021. The unit analysis unit is determined based on the purposive sampling method so that the research data derived from financial statements are one hundred eighty-five. The results showed that operating activity cash flow and financing activity cash flow positively and significantly affect stock returns. The investment activity cash flow and bank size do not affect stock returns. The investment activity cash flow and bank size are not always a concern of investors in making investment decisions and estimating returns in a company. The operating cash flow and financing cash flows are essential indicators for investors in making investment decisions in the capital market. The operating cash flow and financing cash flow act as positive signals on stock returns, especially for related stakeholders.